Economics - Dolan, Edwin G.; Lindsey, David Earl. (Chicago : Dryden Press, 1986)
The book is a complete package of materials for teaching and learning economics. It covers both macroeconomics and microeconomics. This edition reflects the inputs of a great many users of the text at schools across the country.
Rev. ed. of: Basic economics. 3rd ed. 1983.
Includes bibliographical references and index.
aia 13/11/2017
Loans
Keywords: Economics